Analysis of House Sanitation and Hygiene With Malaria Incidence in Nerong Village, Kei Besar Selatan District, Maluku Regency Southeast - Sari Roroa, Indah Kumala; Ukik Agustina (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2025)
The high number of malaria cases in September-December 2023 as many as 82 cases was caused by poor home sanitation and hygiene which are factors related to malaria transmission because they provide a suitable environment as a resting place and breeding place for mosquitoes carrying malaria. The purpose of this study was to determine the relationship between home sanitation and hygiene with the incidence of malaria in Nerong Village, Kei Besar Selatan District, Southeast Maluku Regency. The design of this study is quantitative analytic with a case-control approach. Respondents were taken using a 1:1 case-control study formula with a case sample of 45 people and a control sample of 45 people, so that the total respondents were 90 people. The independent variables were sanitation and home hygiene and the dependent variable was the incidence of malaria. The results of statistical tests used a 2 x 2 chi square table. The results of the study showed that home sanitation was known by most respondents as many as 53 (58.9%) in the category of not meeting requirements. Hygiene was known by most respondents as many as 47 (52.2%) respondents in the category of not meeting requirements. The incidence of malaria was known by half of the respondents as many as 45 (50.0%) in the category of having a history and half of the respondents as many as 45 (50.0%) in the category of having no history. The results of data analysis show that the variable of home sanitation with the incidence of malaria obtained a p value of 0.001 <α = 0.05 and an OR value of 4,230 and the variable of hygiene with the incidence of malaria obtained a p value of 0.005 <α = 0.05 and an OR value of 3,294. Thus, there is a relationship between home sanitation and hygiene with the incidence of malaria. Based on the results of the study, it was concluded that the community must always pay attention to good home sanitation and hygiene in order to avoid malaria. Health workers also always provide information through counseling so that they can increase public knowledge regarding the importance of home sanitation and hygiene.